Examining Inclusive Education Implementation in Indonesian Kindergartens: Between Philosophy and Practice - Hayatiningsih, Diyah; Azizah, Nur (Papanda Publisher, 2025)
Inclusive education implementation in kindergartens faces complex challenges between philosophical commitments and practical capacities. This study examined inclusive education implementation in kindergartens in North Sangatta District, East Kutai Regency, encompassing conceptual, policy, structural, and practical implementation dimensions. Qualitative study with in-depth interviews of four school principals from TK Negeri Pembina, TK Negeri 1, TK Starkidz, and TK Al Muhajirin. Data were analyzed using Miles and Huberman's interactive model through data reduction, data display, and conclusion drawing. All institutions demonstrated accessibility commitments and non-discriminatory practices in student admission. Implementation of differentiated curricula and innovative pedagogical approaches showed positive potential, yet significant gaps emerged in specialized teacher competencies, systematic support structures, and formal policy frameworks. Supporting factors included inclusive classroom atmospheres and parental involvement, while primary barriers were human resource limitations, infrastructure constraints, and teacher knowledge gaps regarding children with special needs. Contradictions exist between philosophical commitments and practical implementation capacities, indicating need for systematic coordination across dimensions for effective inclusive education.